Association Between Carotid Artery Perivascular Fat Density and Embolic Stroke of Undetermined Source - Hu, Xiaohong; Chen, Jianhui; Fu, Huajun; Chen, Yinjuan; Fan, Daofeng; Chen, Yangui; Shen, Chaoxiong (Frontiers in Neurology, 2022)
Aim: This study aims to retrospectively evaluate the association between pericarotid inflammation and the presence of embolic stroke of undetermined source (ESUS). Methods: 126 patients with ESUS and 118 patients with ischemic stroke from large artery atherosclerosis (LAA) were enrolled. All patients underwent brain magnetic resonance imaging and a neck computed tomography angiography (CTA) examination. Reviewers were blinded to infarct location and stroke cause. Paired t-tests assessed within-subjects differences in mean Hounsfield units in carotid perivascular fat between the cerebral infarction side and contralateral side for ESUS and LAA ischemic stroke cases. Unpaired Student’s t-test was used to assess between-subjects differences in mean Hounsfield units between ESUS and LAA ischemic stroke cases. Results: In both ESUS cases and LAA ischemic stroke cases, the pericarotid fat density around the carotid artery ipsilateral to the stroke significantly increased compared with contralateral stroke position in both groups (ESUS cases -56.31±18.70 versus -67.31±20.01, P=0.000; LAA ischemic stroke cases -51.62±19.95 versus -64.58±22.68, P=0.000). However, there was no significant difference in ipsilateral and contralateral positions to infarct between ESUS cases and LAA ischemic stroke cases (ipsilateral to infarct -56.31±18.70 versus -51.62±19.95, P=0.059; contralateral to infarct -67.31±20.01 versus -64.58±22.68, P=0.320). Conclusions: We found increased density in the fat surrounding carotid artery ipsilateral to stroke compared with contralateral in ESUS, suggesting the presence of an inflammatory reaction that extends beyond the vessel lumen in ESUS patients with a risk factor profile similar to LAA strokes.